Effectiveness of cowpea and wild Vigna germplasm distribution and cost implication on their conservation efforts by IITA - Manyong, Victor M.; Dumet, D.; Ogundapo, A.T.; Horna, D. (International Institute of Tropical Agriculture, 2012)
IITA’s Genetic Resources Center (GRC) maintains over 15,000 accessions of cowpea (Vigna unguiculata L.) and wild Vigna which is available and distributed worldwide for research in food and agriculture. Since 1985, IITA has distributed germplasms for cowpea genetic improvement research to institutions in sub-Saharan Africa, Asia, South America, and USA. The present study is the first attempt to assess the effectiveness of cowpea and wild Vigna distribution mechanisms and to estimate cost for the conservation and distribution of the international Vigna collection. This study involved a mail survey conducted mainly amongst partners who collected germplasm from IITA genebank between 1985 and 2007 (referred to as users in this paper) and the application of a Decision Support Tool (DST) for genebank cost evaluation developed by IFPRI. Thirteen percent of the users who received in the range of 84% of the germplasm distributed completed the questionnaires. The results indicate that accessions were used primarily for breeding, agronomy and biotechnology studies. The bulk of these accessions were requested after 2005 and the majority of respondents found it from very easy to easy to access germplasm. Desirable traits most sought by users are high yield and resistance to pests and diseases. Major constraints associated with the distributed accessions were their phytosanitary status and the limited number of seeds provided by GRC. Recommendations were made to upgrade the genebank infrastructure in order to respond to high demand and address the quality issue of accessions. The capital cost represented the big share of the total cost for both cowpea and wild Vigna. Yearly activities of regeneration of accessions and distribution were the major components of operational costs. Increasing the number of accessions in order to reduce the unit cost and upgrading and expanding the current infrastructure would contribute to the efficiency of the IITA genebank. A World Bank funded project aiming at the rehabilitation of the CGIAR’s genebank has initiated such changes.